A Triband Hexagonal Shaped Polarization Insensitive Absorber by Tuning Graphene Material in Terahertz Frequency Domain - Prasad, Nagandla; Pardhasaradhi, Pokkunuri; Madhav, Boddapati Taraka Phani; Raju, Vysyaraju Lokesh; Priya, Pucha Poorna (Progress in electromagnetics research M Pier M, 2023)
Terahertz era is becoming a more prominent and expanding platform for a variety of applications. In this paper, we propose a triband absorber with a hexagon-shaped radiating patch for THz applications. The proposed structure has three layers: a hexagonal patch made of graphene as a radiating patch, a silicon layer as a dielectric substrate, and a bottom conductive layer made of gold to prevent EM wave transmission. The proposed structure operates at three resonant frequencies 0.38 THz, 1.23 THz, and 1.77 THz, respectively. We may accomplish maximum absorption level (above 90%) and maximum absorption bandwidth by setting relevant chemical potential and relaxation times to 0.2 ev and 0.2 ps, respectively. The proposed structure contains a lossy silicon substrate, which has a dielectric constant of 11.9 and a loss tangent of 2.5e-004. The proposed structure is experimented with three layers, and the effect on absorbance for different modes is illustrated.